2019
DOI: 10.1016/j.watres.2018.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the distribution of pharmaceuticals in soil-water-plant systems

Abstract: Pharmaceuticals in agricultural soils originating from irrigation with treated wastewater and landapplied biosolids can enter field crops. However, little is known about the role of pore water in plant uptake of pharmaceuticals from soil. In this study, the fate, uptake and distribution of fifteen commonly used pharmaceuticals in soil-water-radish systems were investigated to examine the relationship between the accumulation and their physicochemical processes in soils. The results indicate that the distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 172 publications
(82 citation statements)
references
References 67 publications
5
77
0
Order By: Relevance
“…For the soil-plant RCF (water) data from laboratory or field studies, only the data for samples with > 7 days (up to 93 days) of exposure were selected, with most data (~85%) having exposure times of 39–70 days. In either case, no RCF (water) data of ionic and ionizable chemicals were selected since their uptakes by plants may involve more than a partition process (Tanoue et al, 2012; Wu et al, 2013; Li et al, 2019). When adopting the soil-plant data from literature, only the studies with reported soil f om and accessible plant f lip values were selected.…”
Section: Sources Of Literature Datamentioning
confidence: 99%
“…For the soil-plant RCF (water) data from laboratory or field studies, only the data for samples with > 7 days (up to 93 days) of exposure were selected, with most data (~85%) having exposure times of 39–70 days. In either case, no RCF (water) data of ionic and ionizable chemicals were selected since their uptakes by plants may involve more than a partition process (Tanoue et al, 2012; Wu et al, 2013; Li et al, 2019). When adopting the soil-plant data from literature, only the studies with reported soil f om and accessible plant f lip values were selected.…”
Section: Sources Of Literature Datamentioning
confidence: 99%
“…The environment can also be polluted by veterinary pharmaceuticals from animal urine or farm waste (e.g., Charuaud et al, 2019). Pharmaceuticals that contaminate soils may subsequently leach to groundwater (e.g., Burri et al, 2019;Godfrey et al, 2007;Fram and Belitz, 2011;Lesser et al, 2018;Li, 2014;Loos et al, 2010) or can be taken up by plants (e.g., Ahmed et al, 2015;Al-Farsi et al, 2017;Christou et al, 2019;Goldstein et al, 2014;Klement et al, 2020;Kodešová et al, 2019aKodešová et al, , 2019bLi et al, 2018Li et al, , 2019aLi et al, , 2019bMalchi et al, 2014;Montemurro et al, 2017;Mordechay et al, 2018;Shenker et al, 2011;Winker et al, 2010;Wu et al, 2013). Further propagation of pharmaceuticals in the environment depends on their sorption and dissipation in the vadose zone (e.g., Carter et al, 2019;Kümmerer, 2009aKümmerer, , 2009bZhi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This work was expanded by Li, Sallach, Zhang, Boyd, and Li (2019) who evaluated the additional complexity of soil in the radish production system. This study showed that bioconcentration in lettuce plant material was positively correlated with soil–water partitioning ( D ow ) for neutral compounds.…”
Section: Antibiotics In Agroecosystemsmentioning
confidence: 99%